Ellagic Acid Activated PPAR Signaling Pathway to Protect Ileums Against Castor Oil-Induced Diarrhea in Mice: Application of Transcriptome Analysis in Drug Screening - Chen, Jianqing; Yang, Hongliang; Sheng, Zunlai (Frontiers in Pharmacology, 2020)
Background Acute diarrhea is still a common and serious disease. The causes of acute diarrhea are very complicated. Therefore, we need to find a medicine to control diarrhea symptoms, save time for diagnosis of pathogens, and prevent drug abuse. Ellagic acid (EA), a natural polyphenol drug, has anti-diarrhea effects. However, the action mechanisms of EA for non-specific diarrhea have not been characterized. Materials and Methods To study the mechanisms of EA, mice were divided into four groups. Group C were intraperitoneally injected with 0.1 ml physiological saline and orally given 0.2 ml physiological saline, and then after experiment began 0.5 h, orally administered 0.3 ml physiological saline. Group D were intraperitoneally injected with 0.1 ml physiological saline and orally given 0.2 ml castor oil, and then after experiment began 0.5 h, orally administered 0.3 ml physiological saline. Group E were intraperitoneally injected with 0.1 ml physiological saline and orally given 0.2 ml castor oil, and then after experiment began 0.5 h, orally administered 0.3 ml EA (10 mg/ml). Group V were intraperitoneally injected with 0.1ml GW9662 (1m g/ml) and orally given 0.2 ml castor oil, and then after experiment began 0.5 h, orally administered 0.3 ml EA (10 mg/ml). Transcriptome were performed on ileum tissues of mice in group D and E. Histological examination and qRT-PCR were performed on ileum tissues of mice in group C, D, E, and V. Results We found that a total of 273 differentially expressed genes (DEGs) were obtained, including 160 up-regulated DEGs and 113 down-regulated DEGs. The DEGs were enriched in 458 Gene Ontology (GO) terms and 15 Kyoto Encyclopedia of Genes and Genomes (KEGG) pathways, respectively. The peroxisome proliferator activated receptor (PPAR) signaling pathway was the most significantly enriched in KEGG pathways. We used the PPAR-specific antagonist GW9662 to validate the anti-diarrhea and anti-inflammatory effect of EA in group V compared with group E. Conclusively, EA protected ileums against castor oil-induced inflammation and diarrhea by activating the PPAR signaling pathway and a method was used to study the mechanism of EA.